Improved survival with radiotherapy in hepatocellular carcinoma with major vascular invasion: A propensity‐matched analysis of Surveillance, Epidemiology, and End Results database. (18th January 2019) - Lin, Qiuyan; Huang, Xiaoquan; Zhong, Canmei; Luo, Tiancheng; Zeng, Xiaoqing; Chen, Shiyao
Abstract: Objectives: Hepatocellular carcinoma (HCC) associated with major vascular invasion is an advanced stage disease with an extremely poor prognosis and low survival rate. Our study evaluated the survival benefit of radiotherapy (RT) in HCC patients with major vascular invasion through Surveillance, Epidemiology, and End Results database. Methods: We analyzed 3181 HCC patients with major vascular invasion cases diagnosed from 2004 to 2013. Patients (N = 308) who underwent RT and patients (N = 2873) who did not receive RT were compared. We successfully analyzed patients using propensity score matching (PSM). Kaplan‐Meier and Cox‐regression analyses were applied to assess prognosis. Results: The median survival time in radiation‐treated group was longer compared to the control group (7 months vs 3 months; P  < 0.001) in the overall sample and 3 months longer compared to the control group (7 months vs 4 months; P  < 0.001) in a PSM cohort. Cox‐regression analyses showed that radiation‐treated patients in propensity‐matched sample had a significantly lower risk of mortality (HR: 0.625, 95% CI: 0.522‐0.749, P  < 0.001) compared with untreated patients. The radiation‐treated groups had better survival rate than untreated group. Subgroup analysis revealed that the survival time of patients in radiation‐treated group was significantly longer than that in the untreated group ( P  < 0.001 and P  = 0.026, respectively). The subgroup analysis also revealed that RT provides a survival benefit regardless of race, marital status, and tumor size after PSM. Conclusions: Radiotherapy provides improves survival in HCC patients with major vascular invasion, especially for tumor(s) confined to one lobe and not on surface of liver. Abstract : We compared radiation‐treated patients and the untreated patients. The results show that RT provides improves survival in HCC patients with major vascular invasion, especially for tumor(s) confined to one lobe and not on surface of liver.